2021
DOI: 10.3389/fcvm.2021.631750
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular Matrix Patches for Endarterectomy Repair

Abstract: Patch repair is the preferred method for arteriotomy closure following femoral or carotid endarterectomy. Choosing among available patch options remains a clinical challenge, as current evidence suggests roughly comparable outcomes between autologous grafts and synthetic and biologic materials. Biologic patches have potential advantages over other materials, including reduced risk for infection, mitigation of an excessive foreign body response, and the potential to remodel into healthy, vascularized tissue. He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 89 publications
0
5
0
Order By: Relevance
“…Extensive studies have shown that implanted biologic materials (such as non-crosslinked decellularized SIS-ECM) stimulate the production of site appropriate, functional tissue (termed “constructive remodeling”[ 37 ])[ 20 - 23 , 36 ]. The ability to elicit a remodeling response post-implantation is due to the natural degradation of the implanted ECM by proteases which release intrinsic bioactive peptides and growth factors such as FGF-2 and VEGF in situ [ 22 , 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Extensive studies have shown that implanted biologic materials (such as non-crosslinked decellularized SIS-ECM) stimulate the production of site appropriate, functional tissue (termed “constructive remodeling”[ 37 ])[ 20 - 23 , 36 ]. The ability to elicit a remodeling response post-implantation is due to the natural degradation of the implanted ECM by proteases which release intrinsic bioactive peptides and growth factors such as FGF-2 and VEGF in situ [ 22 , 38 - 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Synthetic (non-biologic) absorbable and non-absorbable materials have been reported to initiate a strong foreign body reaction, resulting in chronic inflammation leading to hypovascular fibrotic tissue surrounding the implanted material[ 14 - 18 ], which a previously-marketed non-absorbable synthetic envelope leveraged to stabilize the electronic device upon implantation[ 19 ]. Conversely, ECM (the material that the biologic envelope is made from) has been shown to promote constructive remodeling and healthy tissue restoration[ 20 - 23 ]. Both biologic and non-biologic envelopes have been reported to support clinical infection prevention strategies[ 12 , 24 - 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…Different vascular substitutes for diseased artery have been developed, but there is still no material has a similar structure like native artery 23 . As for the vascular patch materials, compared to the prosthetic patch, biological patches have reduced risk for infection, reduced foreign body reaction 24 . Decellularized materials have reduced immunogenicity but preserve the native structure of the organ or tissue, the decellularized scaffold allows cells attachment, migration and proliferation after implantation 25 .…”
Section: Discussionmentioning
confidence: 99%
“…23 As for the vascular patch materials, compared to the prosthetic patch, biological patches have reduced risk for infection, reduced foreign body reaction. 24 Decellularized materials have reduced immunogenicity but preserve the native structure of the organ or tissue, the decellularized scaffold allows cells attachment, migration and proliferation after implantation. 25 Decellularized bovine and porcine pericardium are widely used in clinic, but they are not suitable in some religious F I G U R E 5 Bioinspired fish swim bladder patch decrease neointimal thickness.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the unique properties of each tissue (i.e., specific tissue density), dECM scaffolds from different sources undergo distinctive degradation rates [159]. In this respect, it takes a median of six months for decellularized vessels to undergo ECM regeneration and be fully replaced with new host ECM [25], while SIS-ECM in endarterectomy requires only three months to get fully degraded and replaced with host functional tissues [160]. Therefore, the dECM degradation rate determines the time needed for ECM to be fully replaced with a newly synthesized host ECM.…”
Section: Gagsmentioning
confidence: 99%